Causes and Consequences of Hypertriglyceridemia - Packard, Chris J.; Boren, Jan; Taskinen, Marja-Riitta (Frontiers in Endocrinology, 2020)
Elevations in plasma triglyceride are the result of overproduction and impaired clearance of triglyceride-rich lipoproteins - very low-density lipoproteins (VLDL) and chylomicrons. Hypertriglyceridemia is characterised by an accumulation in the circulation of large VLDL – VLDL1 – and its lipolytic products, and throughout the VLDL-LDL delipidation cascade perturbations occur that give rise to increased concentrations of remnant lipoproteins and small, dense low-density lipoprotein (LDL). The elevated risk of atherosclerotic cardiovascular disease in hypertriglyceridemia is believed to result from the exposure of the artery wall to these aberrant lipoprotein species. Key regulators of the metabolism of triglyceride-rich lipoproteins have been identified and a number of these are targets for pharmacological intervention. However, a clear picture is yet to emerge as to how to relate triglyceride lowering to reduced risk of atherosclerosis.